Prospective teachers' evaluations in terms of using reflective thinking skills to solve problems - Tuncer, Murat; Ozeren, Ender (Elsevier Science Bv, 2012)
The general aim of this research is to evaluate prospective teachers in terms of their use of reflective thinking skills to solve problems. With this aim, the views' of prospective teachers on problem solving and reflective thinking skills has been researched to determine whether there is a significant difference with respect to their gender, departments and classes. As a means of data collection, The Scale of Reflective Thinking Skills to Solve Problems, which was developed by Kizilkaya and Askar (2009), has been used. The study population is prospective teachers who attend the Education Faculty of Firat University. Looking at the opinions of prospective teachers in the different factors of the scale; in the question dimension, in the evaluation dimension, in the reasoning dimension and in the whole of the scale it has been found that there was a significant difference in the class variable. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Ayse Cakir Ilhan
World Conference on Design, Arts and Education (DAE) -- MAY 01-04, 2012 -- Antalya, TURKEY
Keywords: Reflective Thinking; Solving Problems; Teacher Training; Critical Thinking